Reliable mutual node evaluation for trust-based OLSR in tactical MANETs - Lim, Ji Hun; Lim, Keun Woo; Ko, Young Bae (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2018)
This paper proposes a mutual node evaluation method in mobile ad hoc networks to recognize and reliably remove attacker nodes from deteriorating the network. We focus on a tactical networking environment, where the network is generally maintained in harsh and hostile areas while the applications require stringent service requirements. In these kinds of environments, it is desirable to utilize proactive routing methods such as Optimized Link State Routing (OLSR). However, OLSR have weaknesses against various security attacks. To solve this problem, we provide a trust-based evaluation approach where node evaluate each other based on the packet forwarding capabilities. We prove the performance of our proposed method through NS-3.
Keywords: Evaluation approach; Networking environment; Optimized Link State Routing; Packet forwarding; Proactive routing; Service requirements; Tactical network; Trust-based routing; Mobile ad hoc networks; Optimized link state routing; Tactical networks; Trust-based routing